Laser therapy decreases oral leukoplakia recurrence and boosts patient comfort: a network meta-analysis and systematic review - Rui Luo; Yanan Wang; Ruixin Li; Yanan Ma; Haitao Chen; Jian Zhang; Jun Shen (BMC, 2024)
Abstract Background Oral leukoplakia (OLK) is a prevalent precancerous lesion with limited non-pharmacological treatment options. Surgery and various lasers are the mainstay of treatment; however, their relative efficacy and optimal choice remain unclear. This first network meta-analysis compared the effects of different lasers and surgical excision on post-treatment recurrence and comfort in OLK patients. Methods We searched four databases for relevant randomized controlled trials (RCTs) up to April 2023. The primary outcome was post-treatment recurrence, and secondary outcomes included intraoperative hemorrhage and postoperative pain scores. The Cochrane Risk of Bias tool was used to assess the study quality. Meta-analysis and network meta-analysis were employed to determine efficacy and identify the optimal intervention. Results A total of 11 RCTs including 917 patients and 1138 lesions were included. Er,Cr:YSGG laser treatment showed significantly lower recurrence rates compared to CO2 laser (OR: 0.04; 95% CI: 0.01-0.18), CO2 laser with margin extension (OR: 0.06; 95% CI: 0.01-0.60), Er:YAG laser (OR: 0.10; 95% CI: 0.03-0.37), electrocautery (OR: 0.03; 95% CI: 0.00-0.18), and standard care (OR: 0.08; 95% CI: 0.02-0.33). Er,Cr:YSGG laser also ranked the best for reducing recurrence, followed by standard care and CO2 laser combined with photodynamic therapy (PDT). Er:YAG and Er:Cr:YSGG lasers minimized bleeding and pain, respectively. None of the interventions caused severe adverse effects. Conclusion For non-homogeneous OLK, Er:YAG, Er:Cr:YSGG, and CO2 laser combined with PDT offer promising alternatives to surgical excision, potentially reducing recurrence and improving patient comfort. Further high-quality RCTs are necessary to confirm these findings and determine the optimal laser-PDT combination for OLK treatment.